2009
DOI: 10.1039/b819693a
|View full text |Cite
|
Sign up to set email alerts
|

An intriguing hydrogen bond arrangement of polymeric 1D chains of 4,4′-bipyridine coordinated to Co2+, Ni2+, Cu2+ and Zn2+ ions having barbiturate as counterions in a 3D network

Abstract: In this work, four new transition metal complexes of general formula {[M(bipy)(H 2 O) 4 ](B) 2 }(H 2 O) 6 (where M]Co 2+ , Ni 2+ , Cu 2+ and Zn 2+ , B is barbiturate anion and bipy is 4,4 0 -bipyridine) were obtained and investigated by means of single crystal X-ray diffraction and vibrational (Raman and infrared) spectroscopic techniques. The CoB 2 bipy$10H 2 O, NiB 2 bipy$10H 2 O and CuB 2 bipy$10H 2 O basic units give rise to polymers, where Ni(II) and Cu(II) compounds are isomorphous, however all compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
3
14
0
1
Order By: Relevance
“…The ligand p-electrons involved in the bond imply in a strengthening of the CN bond, and consequently in an increase in the bond order, and with a decrease in the bond length. This result is in a good agreement with the coordination of the pyridine nitrogen atoms of 4,4 0 -bipyridine to the metal ion, and is also supported by the comparison with other analogous compounds reported in the literature [9,34]. Other band which can be observed in the spectra is the one at 1295 cm À1 , assigned to the m ring + dCH combination mode of the bpy ligand.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The ligand p-electrons involved in the bond imply in a strengthening of the CN bond, and consequently in an increase in the bond order, and with a decrease in the bond length. This result is in a good agreement with the coordination of the pyridine nitrogen atoms of 4,4 0 -bipyridine to the metal ion, and is also supported by the comparison with other analogous compounds reported in the literature [9,34]. Other band which can be observed in the spectra is the one at 1295 cm À1 , assigned to the m ring + dCH combination mode of the bpy ligand.…”
Section: Resultssupporting
confidence: 87%
“…Garcia et al [9] synthesized the same complexes with Cu 2+ and Ni 2+ metallic ion, and observed the formation of the cavities via hydrogen interaction formed by the two barbiturates anions and four water molecules crystallization encapsulated the covalent [M(bpy)(H 2 O) 4 ] 2+ linear chains. However these cavities were not observed for the FeB 2 bpyÁ10H 2 O (1) and ZnB 2 bpyÁ10H 2 O (2) complexes investigated here, due to the different localization of the crystallization water molecules responsible by the change of the space group in relation to the Cu 2+ and Ni 2+ complexes (P6 5 22).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations